Effect of plant growth regulators on growth and yield of Mukhi Kachu (Bangladesh Journal of Agricultural Research, 2010)
An experiment was conducted with different concentrations of plant growth regulators to evaluate their effects on the growth and yield of late planted Mukhi Kachu (Colocsis esculenta). Different treatments of uniconazole (growth retardant showed significant influence on plant height, petiole length, number of leases per plant, weight of leaf and weight of petioles per hill, number and weight of corms and cormels per hill and yield of cormel. GA3, (growth promoter) enhanced foliage growth, flowering, and cormel development Key Words: Growth regulators; Mukhi Kachu (Colocusis esculenta); yield. DOI: 10.3329/bjar.v34i2.5794Bangladesh J. Agril. Res. 34(2): 233-238, June 2009